Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1016/j.jaut.2010.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Immune regulatory CNS-reactive CD8+T cells in experimental autoimmune encephalomyelitis

Abstract: Immune-based self-recognition and failure to modulate this response are believed to contribute to the debilitating autoimmune pathology observed in multiple sclerosis (MS). Studies from its murine model, experimental autoimmune encephalomyelitis (EAE), have shown that neuroantigen-specific CD4+ T cells are capable of inducing disease, while their immune sibling, the CD8+ T cells, have largely been ignored. To understand their role in autoimmune demyelination, we first confirmed that, similar to our observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
119
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(130 citation statements)
references
References 61 publications
9
119
2
Order By: Relevance
“…Myelin-specific CD8 + T cells have been shown to play a pathogenic role in EAE (38,39). However, more recently, myelin-specific autoregulatory CD8 + T cells have been shown to inhibit EAE, through the suppression of CD4 + T-cell and/or antigen-presenting cell function by direct killing in an antigenspecific manner (40,41). The fact that both FXR agonists increased the CD8 + T-cell population in vivo concurrently with increased PD1, PD-L1, and BTLA expression, suggests that a subset of autoregulatory CD8…”
Section: Discussionmentioning
confidence: 99%
“…Myelin-specific CD8 + T cells have been shown to play a pathogenic role in EAE (38,39). However, more recently, myelin-specific autoregulatory CD8 + T cells have been shown to inhibit EAE, through the suppression of CD4 + T-cell and/or antigen-presenting cell function by direct killing in an antigenspecific manner (40,41). The fact that both FXR agonists increased the CD8 + T-cell population in vivo concurrently with increased PD1, PD-L1, and BTLA expression, suggests that a subset of autoregulatory CD8…”
Section: Discussionmentioning
confidence: 99%
“…Treg subset as well as certain CD8 ? Treg subsets express the IL-2 receptor alpha chain (CD25) [87,[89][90][91]93] and, in some instances, the beta chain (CD122) [32,40,49,53,103,111]. CD44 expression is also upregulated on Tregs [32,61,94,[112][113][114], and its level directly correlates with enhanced CD4 ?…”
Section: Tregs Versus T Memory Cellsmentioning
confidence: 99%
“…And fourth, in at least some autoimmune disease states, disease-specific Tregs seem to expand and accumulate in situ upon disease onset [86,111,[126][127][128][129]. In a study by Godebu et al [123], in vitro-generated Tregs demonstrated self-antigen-driven propagation similar to that of memorylike Tregs when injected into NOD mice, in which a constant pressure exerted by the diabetes-associated autoantigens resulted in the selective expansion of certain clonotypes of Tregs with a skewing of Vb TCR usage.…”
Section: Tregs Versus T Memory Cellsmentioning
confidence: 99%
“…The development of such a model will allow us to overcome the major obstacles to the study of environmental determinants of PBC i.e. the long latency period prior to disease appearance and possibly control additional confounding factors [151] while identifying new therapeutic agents [152][153][154]. …”
Section: Conclusion and Future Viewsmentioning
confidence: 99%